2018
DOI: 10.1111/lam.13096
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Shiga toxin-producing Escherichia coli in pasture-based dairy herds

Abstract: Shiga toxin‐producing Escherichia coli strains (STEC) are food‐borne pathogens. While E. coli O157:H7 is commonly associated with cattle, less is known about the prevalence of non‐O157 STEC serogroups in bovines. This study evaluated the prevalence and virulence status of O157:H7 and six E. coli O‐serogroups (O26, O103, O45, O145, O121, O111) in New Zealand dairy farms using molecular as well as culture‐based methods. Fresh farm dairy effluent (FDE) (n = 36) and composite calf faeces (n = 12) were collected ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Strain isolation confirmed 76.7% of the O26 PCR-positive farms, with those herds not confirmed having a significantly higher minimum C t value than that of herds yielding strains. This isolation rate compares favorably with that reported for clinical isolation ( 26 ) and other livestock studies ( 46 , 47 , 51 , 71 ). A number of practical reasons may account for failed isolation, including the low number of colony picks screened per pat, repeated freeze-thaw before reculture compromising viability, low bacterial concentration, and IMS bead efficacy ( 73 , 74 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Strain isolation confirmed 76.7% of the O26 PCR-positive farms, with those herds not confirmed having a significantly higher minimum C t value than that of herds yielding strains. This isolation rate compares favorably with that reported for clinical isolation ( 26 ) and other livestock studies ( 46 , 47 , 51 , 71 ). A number of practical reasons may account for failed isolation, including the low number of colony picks screened per pat, repeated freeze-thaw before reculture compromising viability, low bacterial concentration, and IMS bead efficacy ( 73 , 74 ).…”
Section: Discussionsupporting
confidence: 85%
“…The high prevalence of O103 positivity was unexpected, but is corroborated by other studies, with O103 found to be a predominant non-O157 serogroup in dairy cattle in New Zealand (46) and Ireland (47), and in beef cattle in the US (48,49), Canada (50), and Australia (44). Despite high serogroup prevalence, recovered O103 isolates from cattle appear to carry stx genes relatively infrequently (44,46,47,49,51) as also observed in the previous Scottish survey (33).…”
Section: Herd Risk Analysissupporting
confidence: 77%
See 1 more Smart Citation
“…For instance, thirty calves from a closed herd in Canada were found to harbor at least one of the seven major STEC serogroups with the predominant being O103 (75.8%) and O157 (70%) [73]. Analysis of composite calf feces collected from 12 dairy farms in New Zealand identified STEC O26 (33%) to be the most prevalent serogroup, followed by O45 (25%), O103 (17%), and O121(9%) [79]. STEC O103 is also being increasingly associated with outbreaks in the US; after the venison-related O103 outbreak in 2010, three recent multistate outbreaks were associated with O103 contaminated ground beef, ground bison meat, and clover sprouts following investigations by the Centers for Disease Control and Prevention and USDA-FSIS [80][81][82][83].…”
Section: Resultsmentioning
confidence: 99%
“…STEC O26:H11 colonize the gut of ruminants, such as cattle, sheep and goats, and other animals including small mammals, birds and domestic pets may act as transient vectors [15,16]. Transmission to humans occurs following the consumption of contaminated food or water, and direct contact with animals or their environment [17][18][19]. There is evidence of personto-person spread in households and institutional settings, and the infectious dose is likely to be similar to that of STEC O157:H7 (10-100 organisms) [20,21].…”
Section: Introductionmentioning
confidence: 99%